Family involvement through learning communities - Aponte Rivera, Adriana; González Barrios, Lourdes; González Barrios, Ivana María (Rastros Rostros, 2022)
In current education, it is essential to articulate inclusion in training processes and thus promote the participation of all those involved (school, family, State, and society in general), therefore, the general objective of the research was to strengthen the participation of the family in the educational processes of the students, through learning communities at the El Corozo headquarters of the Patio Bonito Educational Institution in Montería - Córdoba. The methodology was based on a qualitative approach, under an action research design, to establish the role that the family must assume from the learning communities in favor of their participation and inclusion in the processes that children advance in school. The population was constituted by the educational community already mentioned, the sample was the 21 parents of the 26 boys and girls between 8 and 13 years old, who are enrolled and belong to the 3rd, 4th, and 5th grades of the El Corozo campus. The instruments used were two interviews, one with parents and the other with the guidance teacher, participant observation and a group session; the analysis categories constructed were participation, learning communities and communication; Among the findings, the existence of intuitive learning communities without the direct and formal influence of the educational processes advanced by the school was found, highlighting the need to create support networks that open spaces for family participation in all levels of the institution.
Keywords: inclusive education; participation; family; community; active learning; action plan